The microstructure and high-temperature properties of novel nano precipitation-hardened face centered cubic high-entropy superalloys. (15th March 2018) - Zhang, Lu; Zhou, Yang; Jin, Xi; Du, Xingyu; Li, Bangsheng
Abstract: The present work reports two novel γ′(Ni3 Al type)-enhanced high-entropy superalloys Ni45 − x (FeCoCr)40 (AlTi)15 Hfx (x = 0, 0.2 at.%) with high-entropy fcc (face centered cubic) matrix and γ′ particles microstructure at cast condition. A large number of γ′ particles, with an average diameter size of 52 nm (dendritic regions) and 90 nm (inter-dendritic regions), are homogeneously distributed in a high-entropy fcc matrix and are coherent with the matrix. Attributable to the γ′ particles, the alloys show prominent mechanical properties at both room temperature and high temperatures. Coherent strength and atomic ordering strength are the primary strengthening mechanisms. Graphical abstract: Image 1